Anticoagulant dosing in renal impairment - Harder, S. (Phlebologie, 2015)
Anticoagulants are widely used for prophylaxis and treatment of venous thromboembolism in the elderly, who commonly have renal impairment and other comorbidities. Renal impairment is a risk factor for bleeding and thrombosis during anticoagulant therapy and can influence the balance between the safety and efficacy of such agents. Some anticoagulants, such as fondaparinux and the direct acting oral thrombin inhibitor dabigatran etexilate are contraindicated for use in patients with severe renal impairment (eGFR <30 ml/min). However, also the direct acting oral FXa-inhibitors rivaroxaban, edoxaban and apixaban need caution regarding dosing advice or contraindications when used in patients with renal impairment.
Keywords: Anticoagulation; renal impairment; direct oral anticoagulants; DOAC